Insurgent Subjectivities and Political Empowerment - Notes on Brazilian Hip Hop - Assy, Bethania (Re-visiones, 2024)
The grammar on a phenomenology of social injustice calls for understanding the embroiled connection of subjectivity, experience of injustice, and political community. In the current theoretical debate concerning the subject of a theory of justice, the well-known dichotomies run mainly over between formal universality versus substantial localism; abstract equality versus particular identities. This article aims to reach another dimension on a phenomenology of social injustice. The main claim here is that beyond biopolitical capture, concrete experiences of injustice can engender empowerment and resistance, namely, the political empowerment of the subjects of social injustice. Instead of focusing on biopolitical diagnoses on the victimization as major injured ingredients of historical events massacre, human rights victims of facts, governments, or economic systems, the emphasis on social injustice here relies on reflecting on certain levels of creating empowerment and political resistance by the vulnerable ones. Injustice resisting invisibility and enforcing political empowerment and action will be framed here by constituting subjectivity. The Brazilian hip hop Racionais MC will be particularly considered.
Keywords: Political subjectivity; experience of injustice; resistence; empowerment and political action; Hip Hop Racionais MC